Working Memory Content Is Distorted by Its Use in Perceptual Comparisons. (May 2022) - Fukuda, Keisuke; Pereira, April E.; Saito, Joseph M.; Tang, Ty Y.; Tsubomi, Hiroyuki; Bae, Gi-Yeul
Visual information around us is rarely static. To perform a task in such a dynamic environment, we often have to compare current visual input with our working memory (WM) representation of the immediate past. However, little is known about what happens to a WM representation when it is compared with perceptual input. To test this, we asked young adults ( N = 170 total in three experiments) to compare a new visual input with a WM representation prior to reporting the WM representation. We found that the perceptual comparison biased the WM report, especially when the input was subjectively similar to the WM representation. Furthermore, using computational modeling and individual-differences analyses, we found that this similarity-induced memory bias was driven by representational integration, rather than incidental confusion, between the WM representation and subjectively similar input. Together, our findings highlight a novel source of WM distortion and suggest a general mechanism that determines how WM interacts with new visual input.